Plantas alimentícias não convencionais (Panc) em unidades de conservação (UCS) do Município de Clevelândia, Paraná - Muller, Suzieli Aparecida (2022)
Despite the high agricultural production obtained worldwide, hunger and food insecurity are still major global problems, this scenario worsens as health crises, wars or economic crises occur, factors that directly affect the financial insecurity of the population and consequently access to conventional foods is hampered. The rescue of knowledge about traditional plants, that is, Non- Conventional Food Plants (Panc), is a way to guarantee access to highly nutritious foods that are currently neglected. These species are generally spontaneous, adapt to the most diverse environments, and are treated as “weeds” or “bushes”, often due to the lack of knowledge of their nutraceutical components and the possibility of consumption. The Municipal Natural Parks (MNP) under study (Mozart Rocha Loures, Antônio Sansão Pacheco and Tamarino de Ávila e Silva) are located in the municipality of Clevelândia-PR, and protect a great diversity of species, among which are the Panc, which can be included in the food routine, enabling greater food and nutritional security for local communities. Through the lists of Panc species obtained in the present study, it is possible to characterize the biodiversity of Panc in the Municipal Parks, and so far, 43 Panc species have been identified in the MNP Mozart Rocha Loures, 42 in the MNP Antônio Sansão Pacheco and 53 in the MNP Tamarino de Ávila e Silva. It should be noted the presence of Panc species that are in danger of extinction (Araucaria angustifolia (Bertol.) Kuntze and in a vulnerable state (Cedrela fissilis Vell.), which reinforces the need to know and preserve these species. In possession of this information, actions can be taken to encourage the use of these plants in food diversification, promoting food and nutritional security in the local community, as well as subsidizing future research based on the knowledge generated about the species, carrying out educational activities environment and improvement of management and conservation strategies of the units studied.